Effects of physical activity on self-efficacy of patients with bronchial asthma - Carolin SCHULZE (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2024)
Introduction: Due to higher exposures to fine dust, increased smoking and prevalence of obesity and stress, an increase in the diagnosis of bronchial asthma can be expected, which requires adequate, scientifically tested, alternative therapy methods. The current study investigated the effects of regular physical training on general and disease-specific self-efficacy. Materials and Methods: Overall 82 participants with mild to moderate medicated asthma (63% female, mean age = 41.88 ± 10.43 years) took part in the study. They were randomly divided into three groups: (1) no intervention, (2) progressive muscle relaxation and (3) physical activity intervention. Intervention lasted ten weeks with two units of physical activity or relaxation per week, each lasting 60min. Self-efficacy was measured using the German scales of general and COPD self-efficacy scales. Results: Analysis showed positive influence of group assignment and basic values on general self-efficacy with significant differences between physical activity intervention and control group (p < .001). Conclusions: The present study underlies positive effects of physical activity on the subjective well-being of patients with bronchial asthma. Therefore, it is advisable to consider physical activity as an important component in the treatment of patients with bronchial asthma.